2019
DOI: 10.1080/09589236.2019.1635439
|View full text |Cite
|
Sign up to set email alerts
|

“Are trans men the manliest of men?” Gender practices, trans masculinity andmardānegīin contemporary Iran

Abstract: In this article, I examine how trans men who undergo or plan to undergo medical transition construe their masculinity or mardānegī (I follow IJMES's transliteration guide-Persian to English) in Persian language, through certain gender practices that manifest their manhood as manly, real and psychologically well. I argue that trans men in Iran practice masculinity in ways that is not only in strong entanglement with women but also is distanced from non-trans heterosexual men, trans women and gay men. Drawing on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…The interviewees were assured that their names and details would be kept confidential between the researchers, and anonymity was guaranteed by using pseudonyms in the article. All other ethical guidance was followed, including gaining verbal (as opposed to written) consent, as signing and putting one's name on paper is culturally associated with risk in Iran (Saeidzadeh, 2020). All conversations were conducted, recorded, and transcribed in Persian, before being translated to English by one of the researchers.…”
Section: Data Collectionmentioning
confidence: 99%
“…The interviewees were assured that their names and details would be kept confidential between the researchers, and anonymity was guaranteed by using pseudonyms in the article. All other ethical guidance was followed, including gaining verbal (as opposed to written) consent, as signing and putting one's name on paper is culturally associated with risk in Iran (Saeidzadeh, 2020). All conversations were conducted, recorded, and transcribed in Persian, before being translated to English by one of the researchers.…”
Section: Data Collectionmentioning
confidence: 99%
“…Even though certain social imaginaries have been internalized by communities, scholars have found that social imaginaries can be challenged and changed by new imaginaries propagated by new agencies, or by new interpretations of old teachings (Baderin 2006;Goehring 2019;Qodariah 2016). Recent research found that Pakistani men tend to show their masculinity by posting travel and political content on social media (Salam 2021), while in Iran manhood has been associated with wearing a moustache, and having a revolutionary spirit (Saeidzadeh 2020). For centuries, Nusantara people and Muslims in Indonesia believed that political leadership only suited men and that women should assume reproductive roles in the domestic sphere.…”
Section: On Imaginaries Of Manhood and Womanhoodmentioning
confidence: 99%
“…Other studies report a departure from masculine norms where transgender men construct masculine subject positions by drawing attention to diverse ways to embody masculinity. As Green (2005, 295) argued in his qualitative study of trans men, “maleness and masculinity [are] not the same thing and […] masculinity does not depend on having a male body or having a penis.” Similarly, in a study of trans masculinity in Iran, Saeidzadeh (2019) notes that the transgender men were critical of dominant norms of masculinity and did not seek to conform. Saeidzadeh (2019) reports that transgender men constructed their masculinities in relation to attentiveness to women, and T. J.…”
Section: Contextualizing Trans Masculinitiesmentioning
confidence: 99%
“…As Green (2005, 295) argued in his qualitative study of trans men, “maleness and masculinity [are] not the same thing and […] masculinity does not depend on having a male body or having a penis.” Similarly, in a study of trans masculinity in Iran, Saeidzadeh (2019) notes that the transgender men were critical of dominant norms of masculinity and did not seek to conform. Saeidzadeh (2019) reports that transgender men constructed their masculinities in relation to attentiveness to women, and T. J. Jourian (2017) found that the transgender men in his study desired masculinities that “felt authentic to them,” which often entailed masculinities that were crafted with “intentionality” and “gentleness.”…”
Section: Contextualizing Trans Masculinitiesmentioning
confidence: 99%
See 1 more Smart Citation